2020
DOI: 10.1016/j.csbj.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Structural features and functional implications of proteins enabling the robustness of Deinococcus radiodurans

Abstract: Deinococcus radiodurans can survive under extreme conditions, including high doses of DNA damaging agents and ionizing radiation, desiccation, and oxidative stress. Both the efficient cellular DNA repair machinery and antioxidation systems contribute to the extreme resistance of this bacterium, making it an ideal organism for studying the cellular mechanisms of environmental adaptation. The number of stress-related proteins identified in this bacterium has mushroomed in the past two decades. The new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Consistently, it was reported that a Deinococcus geothermalis mutant lacking the cystine importer system, which is a source of thiols, was more sensitive to an H 2 O 2 treatment [21]. Some studies based on biochemical, pharmacological, or genetic approaches characterised the Trx system in Deinococcus [22][23][24] and indicated that it likely plays an essential role in responses to oxidative stress [25,26]. In a previous review describing Deinococcus antioxidant systems [3], the main TR families were listed, revealing that this bacterial genus possesses a complete Trx system, including a relatively high number of TRs related to Trxs and Prxs.…”
Section: Introductionmentioning
confidence: 73%
“…Consistently, it was reported that a Deinococcus geothermalis mutant lacking the cystine importer system, which is a source of thiols, was more sensitive to an H 2 O 2 treatment [21]. Some studies based on biochemical, pharmacological, or genetic approaches characterised the Trx system in Deinococcus [22][23][24] and indicated that it likely plays an essential role in responses to oxidative stress [25,26]. In a previous review describing Deinococcus antioxidant systems [3], the main TR families were listed, revealing that this bacterial genus possesses a complete Trx system, including a relatively high number of TRs related to Trxs and Prxs.…”
Section: Introductionmentioning
confidence: 73%
“…Comparison of the PprI–DdrO response system with the SOS response system reveals distinctions between them. For one thing, the dimerization of the two repressors depends on the interaction from both NTD and CTD, while the interface of DdrO is much more extensive and CTD dependent ( Lu et al, 2019 ; Chen et al, 2020 ). For another, the dissociation of LexA relies on the autocleavage, which is promoted by the stabilization of autocleavage conformation when RecA is activated after sensing DNA damage and form RecA-ssDNA-ATP filaments ( Butala et al, 2008 , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the RDRM sequence recognition and binding, both variation of the conserved base pairs and length shortening impaired the binding of DG-DdrO. In conclusion, the extended dimeric interaction in DdrO is essential for binding to RDRM-containing sequences ( Makarova et al, 2007 ; Lu et al, 2019 ; Chen et al, 2020 ). Besides, apart from this NTD dimerization, Arjan de Groot also revealed a CTD dimerization of DdrO that is quite different to the already known XRE family proteins such as SinR ( de Groot et al, 2019 ).…”
Section: Repression and Derepression Mechanisms Of The Ppri–ddro Systmentioning
confidence: 93%
“…Deinococcus radiodurans , a non-spore-forming gram-positive bacterium, is well known for its extreme resistance to environmental stresses, including ionizing radiation, oxidative stress, and DNA damage. It has been shown that the robustness of this bacterium is the result of multiple mechanisms, e.g ., enhanced DNA repair capabilities, novel DNA damage responses, effective antioxidation systems, and cellular protection of damaged DNA and proteins [ 24 - 26 ]. Whole-genome sequence data reveal that D. radioduran s encodes one HU protein, DrHU ( DR_A0065 ), which is highly expressed from a leaderless mRNA [ 27 ].…”
Section: Introductionmentioning
confidence: 99%